Analysis of education policies for elementary school children in the industrial revolution 4.0 era - Putri, Kharisma Eka; Tanjungsari, Tita; Hadi, Syamsul (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The era of the industrial revolution 4.0 in the aspect of education that plays an important role is educators or teachers, one of the goals is for students to understand digital literacy. But in this era the role of educators will not be replaced by technology. Because in the practice of learning, educators teach character, morals and role models for students. The purpose of this article is to describe the role of elementary school educators in the era of the industrial revolution 4.0 in accordance with existing policies and the role of parents of elementary school students in the era of the industrial revolution 4.0. This study uses the literature study method, namely by searching for literature from various sources, especially Google Scholar, then analyzing reference sources that are in accordance with the issues raised. An important finding obtained from this research is the increasing professionalism of educators or teachers which will have an impact on increasing the quality of elementary school education in entering the era of the industrial revolution 4.0.